2021
DOI: 10.2196/19511
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone Intervention Based on an HIV Risk Prediction Tool for HIV Prevention Among Men Who Have Sex With Men in China: Randomized Controlled Trial

Abstract: Background eHealth interventions based on risk stratification have not been extensively applied for HIV behavioral interventions among HIV-negative men who have sex with men (MSM). Objective This study aimed to evaluate the efficacy of a mobile phone intervention based on an HIV risk prediction tool in promoting HIV testing and reducing high-risk behavior among HIV-negative MSM in China. Methods We performed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 28 publications
(20 reference statements)
1
26
0
Order By: Relevance
“…Half of all studies (54%, 25/46) deployed website-based interventions. Results were largely in favor of digital strategies including e-testing websites [15] , [16] , [17] , [18] , [19] , study websites [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , online counselling [33] , [34] , [35] , [36] , [37] , [38] , and chatbots [39] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Half of all studies (54%, 25/46) deployed website-based interventions. Results were largely in favor of digital strategies including e-testing websites [15] , [16] , [17] , [18] , [19] , study websites [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , online counselling [33] , [34] , [35] , [36] , [37] , [38] , and chatbots [39] .…”
Section: Resultsmentioning
confidence: 99%
“…Feasibility was reported as HIVST kit uptake by three studies delivering oral self-tests through study websites, and was found to be high at 90%−96% [28] , [29] , [30] . Conversely, due to a relatively low uptake of 48%, a telehealth intervention offering home-based HIVST and web-based video counselling may not represent the ideal HIVST strategy for transgender and non-binary youth; voice call or text message-based counselling may be a preferrable option for this population [36] .…”
Section: Resultsmentioning
confidence: 99%
“…Some innovative interventions, including electronic or internet-based technologies, crowd-sourcing, preexposure prophylaxis (PrEP), and postexposure prophylaxis (PEP), have recently been evaluated among MSM ( 10 - 12 ). Yun et al conducted a randomized controlled trial (RCT) showing that mobile phone interventions based on an HIV risk prediction tool is promising in promoting HIV testing and reducing high-risk behavior among MSM ( 13 ). The same group also demonstrated that an assisted partner notification (PN) strategy could increase uptake of HIV testing among sexual partners of recently diagnosed MSM ( 14 ).…”
Section: Combination Preventionmentioning
confidence: 99%
“…Twelve out of the 17 studies on HIV reported on the cost-effectiveness of the intervention. Variables included were cost per infection averted, 34 36 42 87 cost per QALY, 42 cost per HIV case detected, 84 87 cost per DALY averted, 29 34 36 39 41 83 cost per averted loss-to-follow-up, 30 82 cost per YLS, 81 cost per reduction in male sexual partners 37 and cost per % increase in condom use. 37 …”
Section: Resultsmentioning
confidence: 99%
“…Variables included were cost per infection averted, 34 36 42 87 cost per QALY, 42 cost per HIV case detected, 84 87 cost per DALY averted, 29 34 36 39 41 83 cost per averted loss-to-follow-up, 30 82 cost per YLS, 81 cost per reduction in male sexual partners 37 and cost per % increase in condom use. 37 Cost-effectiveness thresholds, which indicates the maximum amount a country or organisation is willing to pay for a unit of health-outcome, were only applied in studies on HIV. The thresholds ranged between one to five times gross domestic product per capita per DALY averted 29 36 39 41 or per YLS.…”
Section: Acute Febrile Infectionsmentioning
confidence: 99%